CONSCIOUSNEES AND STUDENTS’ VICTORIOUS IN ENGLISH AS A FOREIGN LANGUAGE - Yanti Ismiyati (Universitas Batanghari Jambi, 2017)
Abstract: The purpose of this research is to help the learners to awareness and get the victorious in English-Awarnessin context. Because, conscious learner palys an important rule to help the learners to improve their knowledge in mastery English as the second language. Through the comprehension of material the learners are active to use English in context. Teachers give the big influence in teacing and learning process. Through the right concept of teaching it can improve the students awarness in English as the second language based on the material.On the other hands, the learners have good motivation to develop their knowledge, skill, and increase their capacity to mastery English in context. The method used in this research was theories which relate to the topic discussed. The works that are discussed in this paper have been researched in the library.Keywords :Consciousnees, Students Victorious, Foreign Language